ANALISA PRODUKSI BUDIDAYA UDANG VANNAMEI (Litopenaeus vannamei) PADA TAMBAK PLASTIK DENGAN LUAS YANG BERBEDA DI TAMBAK BUSMETIK SEKOLAH USAHA PERIKANAN MENENGAH (SUPM) NEGERI TEGAL - Agung Widodo; Muhamad Agus; Tri Yusufi Mardiana (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
This study aims to determine differences in production and FCR vannamei shrimp in ponds plastics with widely different. The method used in this study is a survey. The survey was conducted in ponds plastic BUSMETIK SUPM State Tegal, Central Java number 3 pieces pond with an area different from that plot A1 (an area of 1000 m2), plot A2 (area of 800 m2) and plot A3 (area 600 m2) for three (3) maintenance cycle. The production of vannamei shrimp with an area of different A (1000 m2), B (800 m2) and C (600 m2) for 3 cycles of maintenance in the pond BUSMETIK SUPM State Tegal indicate that the harvest vannamei shrimp highest in area ponds A (1000 m2) with average yields 2473.667 kg, followed by the pond area B (800 m2) with yields 1933.667 kg, and the yield was lowest for the vannamei shrimp pond area C (600 m2) with results 1183.667 kg. Results of analysis of variance of the data results of the study (Appendix 4), then the result is that the value of F count (103.112)> F table 5% (5.14) and F table 1% (10.92). FCR value for each area of the pond is still good enough (maximum 1.3). FCR is the smallest value occurs in the pond with an area of 1000 m2, namely (1.2), while in the pond area of 800 m2 and 600 m2 FCR is still quite good value (1,3).Keyword : Vannamei Shrimp, Busmetik, Growth, FCR